2021
DOI: 10.3390/w13040538
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gully Land Consolidation on Phreatic Water Transformation in the Loess Hilly and Gully Region

Abstract: Gully Land Consolidation (GLC) is a proven method to create farmlands and increase crop yields in the Loess Hilly and Gully Region, China. However, GLC influences phreatic water transformation and might cause the farmlands water disasters, such as salinization and swamping. For exploring the influence of GLC on phreatic water transformation and mitigating disasters, a series of indoor experiments were conducted in the artificial rainfall hall. Then, we simulated the phreatic water transformation patterns under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…It not only taps into the potential of effective arable land, facilitates the promotion of large-scale agricultural mechanization and improves agricultural efficiency and productivity but also provides new ways and means of water conservation for the sustainable use of water resources in the watershed [39]. As the ultimate aim is to increase the size of the land and the area of effective arable land, rural areas are often subjected to extensive land leveling, and the hardening of ditches and field roads, but this practice is not fully compatible with the concept of ecosystem protection and sustainable development, resulting in a certain degree of damage to the existing ecological balance in rural areas [1,40,41]. Therefore, it is important to follow the concept and construction requirements of the "Mountains, Rivers, Forests, Field, Lakes and Grasses Form a Community of Life"; to consider the economic and ecological benefits of land remediation work; and to carry out corresponding ecological and environmental management work to ensure the quality of farmland ecosystems [42].…”
Section: Discussionmentioning
confidence: 99%
“…It not only taps into the potential of effective arable land, facilitates the promotion of large-scale agricultural mechanization and improves agricultural efficiency and productivity but also provides new ways and means of water conservation for the sustainable use of water resources in the watershed [39]. As the ultimate aim is to increase the size of the land and the area of effective arable land, rural areas are often subjected to extensive land leveling, and the hardening of ditches and field roads, but this practice is not fully compatible with the concept of ecosystem protection and sustainable development, resulting in a certain degree of damage to the existing ecological balance in rural areas [1,40,41]. Therefore, it is important to follow the concept and construction requirements of the "Mountains, Rivers, Forests, Field, Lakes and Grasses Form a Community of Life"; to consider the economic and ecological benefits of land remediation work; and to carry out corresponding ecological and environmental management work to ensure the quality of farmland ecosystems [42].…”
Section: Discussionmentioning
confidence: 99%
“…Through indoor simulation and outdoor experiments in Yangjuangou of Baota district, it was found that the GLCP dam system could effectively store rainwater, form a gully-diving reservoir, alleviate water shortage, and reduce soil erosion caused by runoff. In addition, the dam land formed after consolidation has good water-storage capacity, which can improve soil dryness (Guo et al, 2021). Calculations of the carbon emissions and carbon storage of Jiulongquangou and Yangwangou in Baota District have shown that the GLCP generally exhibits a carbon-sink effect (Lei and Mu, 2018).…”
Section: Glcp and Eco-environmental Sustainabilitymentioning
confidence: 99%
“…GLC is a kind of land consolidation that is a useful tool to improve land use efficiency by managing unused, inefficient, and degraded land (Xu et al, 2022). Land consolidation has provided an approach for increasing a considerable area of arable land and improving the ecological environment and is widely used worldwide (Asimeh et al, 2020; Celebi et al, 2015; Guo et al, 2021; Moravcová et al, 2017; Pasakarnis & Maliene, 2010; Zhang et al, 2021). Land consolidation importantly affects soil erosion because the land use and slope gradient are altered, and then runoff and connectivity of hydrology and sediment are impacted (Van Oost et al, 2000).…”
Section: Introductionmentioning
confidence: 99%